Job satisfaction among foreign nurses in Saudi Arabia: the contribution of intrinsic and extrinsic motivation factors - Al-Sabhan, Turki Fahd; Ahmad, Norliza; Rasdi, Irniza; Mahmud, Aidalina (Malaysian Public Health Physicians Association, 2022)
Foreign nurses face many challenges at the workplace which may affect their level of job satisfaction. High job satisfaction can ensure the delivery of safe and high-quality health services, while low job satisfaction may result in poor work quality and increases the likelihood of the nurses leaving the service. Therefore, ensuring high level of job satisfaction of the foreign nurses is important, especially in countries which heavily rely on their services, such as Saudi Arabia. This study aimed to determine job satisfaction level among foreign nurses in public hospitals in Hail City, Saudi Arabia, and the contribution of intrinsic and extrinsic motivation factors to their job satisfaction level. A cross-sectional study was conducted among 196 foreign nurses in two large public hospitals in Hail City, Saudi Arabia. Data was collected using anonymous self-administered questionnaire. Descriptive and bivariate analysis were conducted. Most foreign nurses had moderate job satisfaction level. There is significant and positive relationship between three components of intrinsic motivation namely autonomy, mastery, and purpose, and three components of extrinsic motivation which were pay, promotion, and operating conditions, with job satisfaction level. Job satisfaction among foreign nurses in the public hospitals is still not optimal. It is imperative for nursing managers, hospitals directors, and policy makers to focus on the significant intrinsic and extrinsic motivation factors in formulating tailored actions to improve foreign nurses’ job satisfaction.